The Impact Of Haze On Healthcare Utilizations For Acute Respiratory Diseases: Evidence From Malaysia - Hafiz Jaafar; Amirah Azzeri; Marzuki Isahak; Maznah Dahlui (Frontiers Media S.A., 2024)
Indexed by WOS/SCOPUS/ERA